Analisis Angka Kebutuhan Nyata Operasi dan Pemeliharaan Jaringan Irigasi Cimuncang - Raka Priatama; Hartono; Euis Kania Kurniawati (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
Analysis of Real Needs for Operation and Maintenance of the Cimuncang Irrigation Network, Pasirhalang Village, Sukaraja District, Sukabumi Regency. The Cimuncang irrigation network is a canal, main building, and auxiliary buildings that function to provide irrigation water and have a functional area of 299 Ha. However, the current condition of the Cimuncang irrigation area is that there is some damage to the water structures. The Cimuncang irrigation area is included in one of the large irrigation areas which will certainly require a lot of power, supplies and funds to carry out the operation and maintenance of irrigation networks. The results of this study know the Real Needs and Maintenance of the Cimuncang Irrigation Network there are 48.91%, meaning that the performance of irrigation buildings is in the category of heavily damaged, recapitulation of the performance of regulatory buildings, namely 64.1% (moderately damaged) and auxiliary buildings, namely 86% (slightly damaged). , the functional value of the performance of the Cimuncang irrigation canal and road inspection is 71.92%, meaning that the performance of the Cimuncang irrigation canal is included in the category of periodic maintenance that is remedial. The results of the calculation of the RAB for the Real Needs Figures and Maintenance of Irrigation Network activities are Rp. 402,600,000 (Four Hundred Two Million Six Hundred Thousand Rupiah).